1991
DOI: 10.1002/1097-0142(19910215)67:4<915::aid-cncr2820670410>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Combined chemotherapy and radiation therapy in advanced inoperable squamous cell carcinoma of the head and neck. The final report of a randomized trial

Abstract: Between 1983 and 1986, the National Institute for Cancer Research in Genoa and affiliated institutions conducted a randomized study to compare two different ways of combining chemotherapy (CT) and radiation therapy (RT). One hundred sixteen patients were randomized to receive neoadjuvant CT followed by definitive RT (treatment arm A) or alternating CT and RT. In treatment arm A, RT consisted of 70 Gy to the involved areas and 50 Gy to the uninvolved neck at 2 Gy/fraction, five fractions per week. In treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(33 citation statements)
references
References 16 publications
2
30
1
Order By: Relevance
“…Approximately 60% of the patients receive radiation therapy to treat head and neck cancer and most receive the combined therapy so that the development of a series of changes is expected to affect the oral cavity 5 .…”
supporting
confidence: 92%
“…Approximately 60% of the patients receive radiation therapy to treat head and neck cancer and most receive the combined therapy so that the development of a series of changes is expected to affect the oral cavity 5 .…”
supporting
confidence: 92%
“…Induction chemotherapy was despite high remission rates not able to improve overall survival [2,3,8,24,31,38,40]. A significant improvement of local tumor control has been shown for concurrent 5-FU, CDDP, carboplatin, mitomycin C and methotrexate and radiotherapy [3,31,45,47].…”
Section: Introductionmentioning
confidence: 99%
“…Merlano et al [40,41] reported a second trial comparing the alternating regimen with that of neoadjuvant chemotherapy followed by definitive radiation for unresectable head and neck cancer (Table 3). Patients were randomized to alternating chemoradiotherapy delivering 60 Gy of split-course radiation as described above with vinblastine, bleomycin, methotrexate, and leucovorin (VBM) instead of 5-FU/CDDP versus induction chemotherapy with all four courses of VBM given upfront followed by conventionally fractionated radiotherapy to 70 Gy in 2-Gy daily fractions [40,41].…”
Section: Integration Of Chemotherapy With Altered Fractionationmentioning
confidence: 99%